Gerakan “ATIKA” Makanan Ibu Hamil di Puskesmas Tungkal II Kabupaten Tanjung Jabung Barat - Arnati Wulansari; Sri Ramadhani; Fajar Rahmawati; Zafira Zafira; Fusvi Sintia Dewi (Jurnal Abdimas Kesehatan (JAK), 2022)
Lack of hemoglobin levels in pregnant women is one of the health problems that are prone to occur during pregnancy and can increase the risk of low birth weight babies (LBW), the risk of bleeding before and during delivery, and can even cause the death of mothers and babies if the pregnant woman suffering from severe anemia. Anemia that is often experienced by pregnant women is due to iron deficiency because in pregnant women there is a twofold increase in iron due to an increase in blood volume without plasma volume expansion to meet the needs of the mother and fetal growth. One of the factors that can affect hemoglobin levels is the type of food consumed. Types of foods that are rarely consumed but are very beneficial for pregnant women are liver, eggs, and fish which can be abbreviated as "ATIKA". Emodemo is a method that can be used to convey information in the form of demonstrations that are attractive and fun for the target audience, because what is being done is not material but role-play and discussion. The result that the target understood the material presented and was able to practice measuring the amount of food consumption of iron sources. It is suggested that the Community Health Centre Tungkal II can increase the activities of education that interactive and interesting related nutritional problems that occur in pregnant women